2000
DOI: 10.1046/j.1364-3703.2000.00007.x
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of carbohydrate partitioning during the interaction of potato virus Y with tobacco

Abstract: To test whether carbohydrates may play a signalling function during plant pathogenesis, we investigated the interaction between tobacco and potato virus Y (PVY(N)). Four days after PVY(N) infection, leaves started to accumulate soluble sugars and leaf photosynthesis decreased. The accumulation of soluble sugars was accompanied by an induction of cell wall invertase and a gradual decrease in the sucrose-to-hexose ratio. In parallel to changes in carbohydrate metabolism and photosynthesis, transcripts encoding P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
107
0
6

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 139 publications
(124 citation statements)
references
References 45 publications
11
107
0
6
Order By: Relevance
“…Transcripts of the acidic, salicylate-inducible protein PR-1b (Herbers et al, 1996(Herbers et al, , 2000 accumulated at the infection site in the wild type from an early stage of infection on, whereas the expression of PR-1b was weaker and only slightly induced in cwINV-deficient plants (Fig. 4A).…”
Section: Impaired Defense Reactions Hypersensitive Cell Death and Dmentioning
confidence: 99%
See 3 more Smart Citations
“…Transcripts of the acidic, salicylate-inducible protein PR-1b (Herbers et al, 1996(Herbers et al, , 2000 accumulated at the infection site in the wild type from an early stage of infection on, whereas the expression of PR-1b was weaker and only slightly induced in cwINV-deficient plants (Fig. 4A).…”
Section: Impaired Defense Reactions Hypersensitive Cell Death and Dmentioning
confidence: 99%
“…In source leaves, constitutive expression of cwINV leads to the accumulation of carbohydrates and a metabolic source-to-sink shift. These plants also show increased gene expression of PR proteins and enhanced resistance against viral infection (Herbers et al, 1996(Herbers et al, , 2000.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The disturbance of chloroplast functions may be responsible for the production of chlorosis that is associated with virus infection [19]. Several plant-virus interaction studies have revealed that virus infection inhibits host photosynthesis, which is usually accompanied by viral symptoms [7,9,10,16,29]. Virus infection commonly causes chlorosis resulting into impaired chlorophyll biosynthesis and reduced photosynthetic activities that lead to a decrease in biomass production and significant loss in crop yield [44].…”
Section: Introductionmentioning
confidence: 99%